2013
DOI: 10.5603/fhc.2013.0010
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the expression of telomerase and prostate-specific membrane antigen in non-advanced prostatic cancer

Abstract: Early recognition of prostate cancer (PC) based on biological markers could be helpful in identification of differences in benign and malignant lesions and facilitate further precise indication for more aggressive treatment. Therefore, the aim of our study was to assess expression of hTERT (human telomerase reverse transcriptase, a catalytic subunit of telomerase) and prostate-specific membrane antigen (PSMA), both considered to be markers of tumor aggressiveness. 140 low advanced PC specimens from patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
(60 reference statements)
2
7
1
Order By: Relevance
“…This may be true, as we observed it in our patients with anaplastic tumours, the highest PSA levels and the lowest nuclear hTERT expression [15]. Earlier we showed that higher PSMA expression in higher pTNM stages and tumour grades may indicate PSMA as a good marker of biological aggressiveness suitable for patients' selection for more aggressive treatment [15]. However, now we are unable to show utility of PSMA for predicting patients' prognosis for BRFS which is in agreement with some studies [22].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…This may be true, as we observed it in our patients with anaplastic tumours, the highest PSA levels and the lowest nuclear hTERT expression [15]. Earlier we showed that higher PSMA expression in higher pTNM stages and tumour grades may indicate PSMA as a good marker of biological aggressiveness suitable for patients' selection for more aggressive treatment [15]. However, now we are unable to show utility of PSMA for predicting patients' prognosis for BRFS which is in agreement with some studies [22].…”
Section: Discussionsupporting
confidence: 63%
“…Another explanation for our results is a hypothesis that telomerase activity is regulated by androgens and the wild-type human androgen receptor inhibits the expression of hTERT in the presence of androgen receptor agonists [30]. This may be true, as we observed it in our patients with anaplastic tumours, the highest PSA levels and the lowest nuclear hTERT expression [15]. Earlier we showed that higher PSMA expression in higher pTNM stages and tumour grades may indicate PSMA as a good marker of biological aggressiveness suitable for patients' selection for more aggressive treatment [15].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The relevance of the present study relies on the combination of genetic data with expression and localization studies. In particular, WB data have been obtained for the first time in human thyroid tumor tissues, whereas IHC analyses for TERT have been previously performed in several normal and neoplastic human tissues, with discordant results concerning the immunolocalization of hTERT, reported to be exclusively nuclear (Ito et al, 2005;Lantuejoul et al, 2004;Preto et al, 2004) or both cytoplasmic and nuclear (Gasinska et al, 2013;Kyo et al, 2003;Mavrommatis et al, 2005). The discrepancies are likely to be mainly due to the different antibodies (Ab) used, since around 15 different monoclonal and polyclonal Ab are available (Fabricius et al, 2009), which are directed against different portions of the protein.…”
Section: Discussionmentioning
confidence: 95%